Modern Lithuanian foreign policy: the adjustment of traditional policy - Batorshina Irina; Volovoy Vadim (Baltic Region, 2011)
The authors consider the core areas of Lithuanian foreign policy. Special attention is paid to the adjustment of the major foreign policy vector, which concentrated earlier on the cooperation with the United States of America and strategic partnership with the Republic of Poland. The article analyses the attempts of Lithuanian president Dalia Grybauskaitė to formulate the so-called «new foreign policy» based on the multivector approach to the intergovernmental cooperation. This research is timely because of an increasing influence of small states on foreign policy decision-making within the European Union. It emphasizes the need to analyse foreign policy priorities of the Baltic States and Central and Eastern European countries and to identify the dominant trends in the international policy in the region in order to forecast further development at European and global levels. This objective is achieved with the help of an integrated approach with elements of interdisciplinary research. Special attention is paid to the comparative-historical approach, which facilitates the analysis of the relations between the Republic of Lithuania and the neighbouring states and its principal partners. Alongside traditional methods of historical research, this work employs such methods as participant observation, content and event analysis, and simultaneous and comparative analysis. The research and practical significance of this work is explained by its emphasis on the need to apply an additional theoretical framework to studies into the foreign policy initiatives of the Republic of Lithuania in the international arena. While earlier they were determined by the value (democratic approach), which was a reflection of American realism, today an increasingly important factor is the personality of the president, who does not always positively influence the changing policy of the country. The results of the research contribute substantially to the understanding of foreign policy processes taking place in Lithuania and the region in general.